General health of under and over 45-year-old patients with coronary artery diseases - Razieh Parizad; Asghar Mohammadpoorasl; Mina Hosseinzadeh; Elnaz Javanshir; Mohammad Hasan Sahebihagh (Wolters Kluwer Medknow Publications, 2021)
Introduction: As a major cause of mortality, coronary artery diseases (CAD) have become an important health priority in recent years. They can affect physical, mental, and social aspects of health and one's perception of wellness and general health. The present study is aimed at determining and comparing the general health status of coronary artery patients in two age groups: Under 45 and 45 and older. Methods: This descriptive-analytical study was conducted with 368 participants. The subjects were selected from March to June 2018 using convenience sampling from Tabriz's Madani Heart Center and Shohada Hospital and then divided equally into four groups: Under 45 CAD patients; under 45 non-CAD patients; 45 and older CAD patients; and 45 and older non-CAD patients. The non-CAD patients were matched to the CAD patients regarding age (±3 years) and sex. The data collection instrument was a 28-item General Health Questionnaire that was administered in interviews with the participants. The data were analyzed using descriptive and analytical statistics. Results: The general health mean scores of the participants were as follows: under 45 CAD patients (41.75 ± 8.80) and their counterpart control group (61.35 ± 7.65); 45 and older CAD patients (40.02 ± 11.22) and their counterpart control group (65.40 ± 6.45). There was a significant difference between the scores of the case and control groups in both age groups (P < 0.001). Conclusion: The results showed that disruption of general health is one of the influential factors in the incidence of CAD. To prevent such diseases, special attention should be given to the instruction of the factors that affect general health and its improvement.